Effects of concurrent eccentric overload and high-intensity interval training on team sports players’ performance - Sanchez-Sanchez, Javier (Array, 2019)
The aim of the study was to compare the effects of an in-season five weeks of high-intensity training (HIT) with a concurrent HIT eccentric overload training (CT) program on male amateur team-sports players’ fitness performance. Twenty-two athletes were randomly assigned to HIT (n=10) or CT (n=12). Both groups completed a HIT program. The CT group also completed two-three sets of six repetitions of eccentric overload training. Before and after training, performance was assessed for change of direction ability (COD), repeated sprint ability for best time (RSAb), mean time (RSAm) and slowest time (RSAs), jumping, and shuttle-run performance. Within-group analyses in both groups showed substantial better scores on COD, RSAb and RSAm and shuttle-run performance. Between-group analyses showed greater improvements in COD, RSAb, RSAm, RSAs, and jumping after additional CT compared to solely HIT. In conclusion, compared to HIT alone, concurrent eccentric overload and HIT training within the same session improved COD, RSA, jump, and shuttle-run performance in basketball and soccers amateur players.